SOFT TISSUE BALANCING IN TOTAL HIP ARTHROPLASTY. - Pencho Kosev; Bojan Valentinov; Yordan Andonov; Cvetan Sokolov (Peytchinski Publishing, 2015)
We present our experience with the soft tissue balancing in total hip arthroplasty. Detailed indications, planning and surgical technique are presented. The described procedures are performed on 278 hips for a period of 6 years (2008-2014). We conclude that the outcome of a THA can be improved by balancing the stability, ROM, muscle strength and limb length equality.